Accuracy of a reverse dot blot hybridization assay for simultaneous detection of the resistance of four anti-tuberculosis drugs in Mycobacterium tuberculosis isolated from China - Li Wan; Qian Guo; Jian-Hao Wei; Hai-Can Liu; Ma-Chao Li; Yi Jiang; Li-Li Zhao; Xiu-Qin Zhao; Zhi-Guang Liu; Kang-Lin Wan; Gui-Lian Li; Cha-Xiang Guan (BMC, 2020)
Abstract Background Drug resistant tuberculosis poses a great challenge for tuberculosis control worldwide. Timely determination of drug resistance and effective individual treatment are essential for blocking the transmission of drug resistant Mycobacterium tuberculosis. We aimed to establish and evaluate the accuracy of a reverse dot blot hybridization (RDBH) assay to simultaneously detect the resistance of four anti-tuberculosis drugs in M. tuberculosis isolated in China. Methods In this study, we applied a RDBH assay to simultaneously detect the resistance of rifampicin (RIF), isoniazid (INH), streptomycin (SM) and ethambutol (EMB) in 320 clinical M. tuberculosis isolates and compared the results to that from phenotypic drug susceptibility testing (DST) and sequencing. The RDBH assay was designed to test up to 42 samples at a time. Pearson's chi-square test was used to compute the statistical measures of the RDBH assay using the phenotypic DST or sequencing as the gold standard method, and Kappa identity test was used to determine the consistency between the RDBH assay and the phenotypic DST or sequencing. Results The results showed that the concordances between phenotypic DST and RDBH assay were 95% for RIF, 92.8% for INH, 84.7% for SM, 77.2% for EMB and the concordances between sequencing and RDBH assay were 97.8% for RIF, 98.8% for INH, 99.1% for SM, 93.4% for EMB. Compared to the phenotypic DST results, the sensitivity and specificity of the RDBH assay for resistance detection were 92.4 and 98.5% for RIF, 90.3 and 97.3% for INH, 77.4 and 91.5% for SM, 61.4 and 85.7% for EMB, respectively; compared to sequencing, the sensitivity and specificity of the RDBH assay were 97.7 and 97.9% for RIF, 97.9 and 100.0% for INH, 97.8 and 100.0% for SM, 82.6 and 99.1% for EMB, respectively. The turnaround time of the RDBH assay was 7 h for testing 42 samples. Conclusions Our data suggested that the RDBH assay could serve as a rapid and efficient method for testing the resistance of M. tuberculosis against RIF, INH, SM and EMB, enabling early administration of appropriate treatment regimens to the affected drug resistant tuberculosis patients.